Learning about citizenship (Journal of Parents and Teachers, 2014)
The classroom is a space for practising citizenship. For this reason, this article presents a large number of activities related to the practice of citizenship in the classroom. The activities deal with the themes of rights and obligations around equality before the law and living together in solidarity; they also work with the figure of the ombudsman.
Keywords: citizenship; activities; classroom; equality before the law; education; rights